Impact of different ectopic fat depots on cardiovascular and metabolic diseases. Issue 12 (20th May 2019) - Ferrara, Daniele; Montecucco, Fabrizio; Dallegri, Franco; Carbone, Federico
Abstract: A growing body of evidence is pointing out the pathophysiological role of fat accumulation in different organs. Ectopic fat depots within heart, liver, skeletal muscle, kidney, and pancreas as well as around blood vessels might be more associated to cardiometabolic risk than classical variables, such as body mass index. Among different mechanisms, lipid metabolism appears to be particularly influenced by ectopic fat depots. Indeed, intracellular accumulation of nonesterified fatty acids, and triglycerides promotes endoplasmic reticulum stress, mitochondrial uncoupling, oxidative stress, and altered membrane composition/function, finally promoting inflammatory response and cell death. The dysfunctional adipose tissue was shown to induce both local and systemic effects, with relevant clinical consequences. Epicardial fat and myocardial steatosis have been associated with the development of atrial fibrillation and ventricular dysfunction. Similarly perivascular adipose tissue appears to trigger atherosclerosis and hypertension. Nonalcoholic fatty liver disease has been recognized both as the hepatic manifestation of metabolic syndrome and as a cardiovascular (CV) risk factor. Importantly, the renal sinus fat emerged as a potential player in kidney dysfunction. Finally, both skeletal muscle and pancreatic fat depots have been indicated as potential endocrine modulators of insulin resistance. Considering the global rise in the prevalence of obesity, the understanding of mechanisms underlying ectopic fat accumulation represents an urgent need, with potential clinical implications for CV risk stratification. Here, we attempt to update the current knowledge of the different ectopic fat depots, focusing on underlying mechanisms and potential clinical implications. Abstract : Ectopic fat depots within heart, liver, skeletal muscle, and pancreas might be more associated to cardiometabolic risk than classical variables The understanding of mechanisms underlying ectopic fat accumulation represents an urgent need, with potential clinical implications for cardiovascular risk stratification